The Effect of Problem-Based Learning (PBL) on Junior High School Students’ Problem-Solving Skills: Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Kemampuan Pemecahan Masalah Siswa SMP - Wyta Ramadisya; Rita Aryani; Luluh Abdillah Kurniawan (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2025)
This study aimed to examine the effectiveness of Problem-Based Learning (PBL) in improving eighth-grade students’ problem-solving skills in Social Studies at SMP Negeri 35 Bekasi. The study was motivated by students’ low problem-solving ability, which has been influenced by the dominance of conventional instruction. A quantitative approach was employed using a quasi-experimental Nonequivalent Control Group design involving 62 students, divided into an experimental group taught with PBL and a control group taught with conventional methods. Data were collected through a 20-item multiple-choice test validated by experts and confirmed reliable, supported by classroom observation. The data were analyzed using prerequisite tests, an independent samples t-test, and N-Gain. The results indicated that the experimental group achieved a higher posttest mean score (83.24) than the control group (75.32). The experimental group also demonstrated a moderate N-Gain and outperformed the control group in learning improvement. These findings confirm that PBL is effective as an alternative strategy in Social Studies to strengthen students’ problem-solving and critical-thinking skills.